Off the coast of Angmagssalik, Greenland. Postcard # 1 from The Danish Missionary Society : Udenfor kysten ved Angmagssalik, Grønland. Postkort nr. 1 fra Det danske Missionsselskab - Buchhave, Th. (University of Southern California Digital Library (USC.DL), 2015)
Off the coast of Angmagssalik, Greenland. Postcard # 1 from The Danish Missionary Society